CARDIOVASCULAR DIAGNOSIS IN PATIENTS WITH RHEUMATOID ARTHRITIS, PRIMARY SJOGREN‘S SYNDROME, SYSTEMIC SCLEROSIS AND SYSTEMIC LUPUS ERHYTEMATOSUS - Vasilev, Vladimir; Bošković, Nikola; mehmedbegovic, zlatko; Radivčev, Aleksandar; Ristić, Arsen (Medicinski podmladak, 2021)
Cardiovascular diseases (CVD) are the leading cause of death in the world and the most common type of comorbidity in patients with systemic lupus erythematosus (SLE), primary Sjögren's syndrome (SjS), systemic sclerosis (SSc), and rheumatoid arthritis (RA). Chronic inflammation in systemic rheumatic diseases can contribute to the development of CVD. Although risk factors for the CVD in the general population are well known, in patients with chronic rheumatic diseases risk factors for the CVD have not been specified as well as their connection with traditional risk factors, which would explain the increased incidence of CVD in these patients.Patients with chronic rheumatic diseases (RA, SLE, SjS and SSc) have an increased risk of developing both coronary and carotid atherosclerotic diseases. With the increase of the world's population suffering from rheumatoid autoimmune diseases, and thus increased morbidity and mortality, an adequate diagnostic strategy for the detection of coronary heart disease and risk stratification for their development is necessary. Functional techniques are readily available and can prove the presence of ischemia. In recent years, increasing attention has been paid to anatomical techniques that determine the degree of atherosclerosis. So far, a small number of studies are known that indicate the diagnostic accuracy and importance of functional and anatomical techniques in patients with autoimmune rheumatic diseases. The advantage of anatomical techniques is reflected in the direct visualization of either obstructive or non-obstructive (subclinical) coronary disease, allowing the detection of atherosclerosis in the early subclinical stage. However, information on the hemodynamic consequences of the detected changes remains unknown without functional testing. In asymptomatic patients with autoimmune rheumatic diseases, studies have shown an increased prevalence of silent ischemia and atherosclerosis and thus suggested early screening in the general population. Unfortunately, only a small number of prospective studies that have examined improved prognosis based on screening. Therefore, it is very important to conduct large prospective studies in terms of examining predictive markers of the occurrence and development of coronary heart disease in patients with autoimmune rheumatoid diseases.
Keywords: heart disease; chronic rheumatic diseases; cardiovascular diagnosis; cardiovascular risk